Synthesis and characterisation of chalcone derivatives and their antioxidant activity - Chang, Ling Ying (2022)
Chalcones (1,3-diphenyl-2-propen-1-ones) have been reported to possess a broad spectrum of biological activities that are associated to their unique core structure consisting of two aromatic rings attached by an α,β-unsaturated carbonyl system. Several evidence have demonstrated that the chalcone derived Mannich bases showed enhanced biological activities than their parent chalcone compounds. In this study, a series of chalcones and their Mannich base derivatives has been synthesized and assessed for their antioxidant activity. The synthesis of chalcones was performed by Claisen-Schmidt condensation of 4’- hydroxyacetophenone and benzaldehyde derivatives. The synthesis of Mannich bases was carried out through Mannich reaction between the synthesized chalcones, formaldehyde and secondary amines including dimethylamine, pyrrolidine and piperidine. The synthesized compounds were characterized using FTIR, LC-MS and NMR spectroscopy. The synthesized chalcone derivatives are 3-(4-chlorophenyl)-1-(4-hydroxyphenyl)-prop-2-en-1-one (CA) and 1-(4-hydroxyphenyl)-3-phenyl-prop-2-en-1-one (CA2). The synthesized Mannich bases using CA as parent compound are 3-(4-chlorophenyl)-1-{3- iii [(dimethylamino)methyl]-4-hydroxyphenyl}-prop-2-en-1-one (DA), 3-(4- chlorophenyl)-1-{4-hydroxy-3-[(pyrrolidin-1-yl)methyl]phenyl}prop-2-en-1- one (PY) and 3-(4-chlorophenyl)-1-{4-hydroxy-3-[(piperidin-1- yl)methyl]phenyl}-prop-2-en-1-one (PI). The Mannich bases derived from CA2 include 1-{3-[(dimethylamino)methyl]-4-hydroxyphenyl}3-phenylprop-2-en-1- one (DA2), 1-{4-hydroxy-3-[(pyrrolidin-1-yl)methyl]phenyl}-3-phenylprop-2- en-1-one (PY2) and 1-{4-hydroxy-3-[(piperidin-1-yl)methyl]phenyl}-3- phenylprop-2-en-1-one (PI2). Antioxidant activity evaluation was performed on the synthesized compounds using DPPH antioxidant assay. The results indicated that chalcone derived Mannich bases exhibited better antioxidant activity than their corresponding chalcone parent compounds. The Mannich bases PY and PY2 showed IC50 values at 550 and 700 ppm, respectively, whereas their parent compounds CA and CA2 showed IC50 values at above 1000 ppm.